2002
DOI: 10.1097/00003226-200210000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Intracameral Amphotericin B Injection in the Management of Deep Keratomycosis

Abstract: Preliminary experience suggests that intracameral injections of amphotericin B may have a role in the management of deep keratomycosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
54
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 16 publications
2
54
0
1
Order By: Relevance
“…In one case healing occurred with formation of corneal opacity while the other two required therapeutic keratoplasty. Kuriakose et al [7] reported complete healing in three out of four patients with intracameral amphotericin B. Hence, intracameral amphotericin B has some role in management of keratomycosis.…”
Section: Discussionmentioning
confidence: 98%
“…In one case healing occurred with formation of corneal opacity while the other two required therapeutic keratoplasty. Kuriakose et al [7] reported complete healing in three out of four patients with intracameral amphotericin B. Hence, intracameral amphotericin B has some role in management of keratomycosis.…”
Section: Discussionmentioning
confidence: 98%
“…(6,8) Generally, prolonged and intensive topical and systemic antifungal therapy is required to eradicate the fungal infections. Contemporary antifungal drugs in the treatment of mycotic keratitis are less effective than contemporary antibacterial drugs in the treatment of bacterial keratitis.…”
Section: Discussionmentioning
confidence: 99%
“…Intracorneal and intracameral injections of amphotericin B. (6,7,8,9) and Intracameral Amphotericin-B. (6,8) were tried in fungal keratitis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the small sample size and correspondingly limited statistical power, the authors recommended larger randomized clinical trials to help resolve the roles of both intracameral antifungal administration and anterior chamber irrigation in the management of severe keratomycosis. [25][26][27][28][29] Together, these studies highlight both the challenges of treating infectious keratitis and the promise and importance of novel therapeutic approaches. For now, intensive, topical antimicrobial therapy remains the mainstay of treatment.…”
mentioning
confidence: 99%